A RELATIVE ASSESSMENT OF THE CONTRIBUTIONS OF AGRICULTURE, OIL AND NON-OIL TAX REVENUES TO NIGERIA’S ECONOMIC EXPANSION - OMODERO, Cordelia Onyinyechi (Annals of Spiru Haret University. Economic Series, 2019)
The decline in oil prices globally has led to diversification of economy in most oil enriched countries. In Nigeria, more attention is given to agriculture and non-tax revenue sources to ensure that the country overcomes a mono-economy syndrome which has affected the nation in the past. This study assesses the contributions of agriculture, oil and non-oil tax revenue to economic expansion in Nigeria using data that cover a period from 1981 to 2017. The regression results indicate that oil revenue has a significant negative impact on economic growth which is represented by gross domestic product. On the contrary, the study finds evidence that agriculture and non-oil tax revenue have a robust significant and positive influence on economic growth. Therefore, the study suggests that tax administration in Nigeria should be more business-growth conscious and that agriculture should be given a boost by creating an enabling environment that could attract foreign direct investments in the agricultural sector. The study also recommends that oil revenues should be utilized for reinvestments into other sectors of the economy. Keywords: Oil revenue, non-oil tax revenue, agriculture, economic growth, Nigeria. JEL Classifications: H27, H24, H25, N5, O4